Minimizing Students’ Anxiety In Learning Speaking English - Rohman, Fazlur (Journal of English Teaching, Literature, and Applied Linguistics, 2019)
Many students, when they learn speaking English, tend to be silent and just listen what the teacher are saying. They do not have willingness to communicate each other or to the teacher. They just want to speak up when the teacher asks them about something. They have a hunch that they fear if their friends will be laughed them when they will have some mistake in speaking, feel nervous when they have to begin the speaking and their vocabularies are limited. When the students have a situation like that, it can make the students have not been able to speak effectively. These situations are about students’ anxiety. Anxiety is about fear, worry, nervous, and self doubt. When speaking class cannot run well because of students’ anxiety, the activity cannot run as well as the teacher has planned before. It will be out of plan and a serious condition because speaking is a crucial part of communication in which students learn language by interacting during the lesson. Conducting communicative tasks is recommended by the writer because it can minimize students’ anxiety in learning speaking English because it is interesting. The students can feel happy and enjoy the learning activity. The students can explore their language especially in English. There is no restriction on the language used here. Students can practice the language directly in the real life in their classroom activity spontaneously. Interaction between teacher and students and among the students can be created.